2018
DOI: 10.1111/bjd.16217
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain in pachyonychia congenita: evidence for neuropathic origin

Abstract: Although thermal and mechanical hypoaesthesia may result from thicker skin, its presentation in painful regions, along with mechanical hyperalgesia and allodynia, point towards the possibility of neuropathic changes occurring in PC. The clinical features and DN4 scores support this possibility and therefore neuropathic pain medications may be beneficial for patients with PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
0
27
0
3
Order By: Relevance
“…61 This pain has been described as sharp, burning, throbbing, or tingling sensations in the affected areas of the feet, which is often exacerbated by mechanical force, such as walking or standing. 62,63 The pain seems to be independent of severity of hyperkeratosis. It can be so severe that many individuals will crawl or use a wheelchair to minimize discomfort.…”
Section: Diverse Pain Phenotypes In Hereditary Palmoplantar Keratodermentioning
confidence: 98%
See 2 more Smart Citations
“…61 This pain has been described as sharp, burning, throbbing, or tingling sensations in the affected areas of the feet, which is often exacerbated by mechanical force, such as walking or standing. 62,63 The pain seems to be independent of severity of hyperkeratosis. It can be so severe that many individuals will crawl or use a wheelchair to minimize discomfort.…”
Section: Diverse Pain Phenotypes In Hereditary Palmoplantar Keratodermentioning
confidence: 98%
“…A survey conducted using the International Pachyonychia Congenita Research Registry revealed that 89% of individuals with PC experience plantar pain and this figure was 97% for those over the age of 10 years who had PC . This pain has been described as sharp, burning, throbbing, or tingling sensations in the affected areas of the feet, which is often exacerbated by mechanical force, such as walking or standing . The pain seems to be independent of severity of hyperkeratosis.…”
Section: Diverse Pain Phenotypes In Hereditary Palmoplantar Keratodermasmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure on affected areas of the soles is painful, often causing patients to limit their activity. Mechanisms of pain in PC have recently been elucidated with pathologic, functional, and questionnaire studies supporting that pain in PC is neuropathic in nature . With the phenotype of chronic pain and focal hypersensitivity in affected skin, PC is an attractive model system to study expression of NOP‐R distribution and assess whether targeting NOP‐R has potential for the treatment of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…The first study to characterize PC pain used pain questionnaires and quantitative sensory testing in 35 patients and concluded that the majority of patients with PC experience pain that has a neuropathic component . In this issue of the BJD , Silviu Brill and colleagues from the Tel Aviv Medical Centre present the results of a second, larger study using pain questionnaires and sensory testing in 62 patients with mutations in KRT6A or KRT16 compared with 45 controls . The authors found an association between PC and moderate‐to‐severe chronic pain, thermal and mechanical hypoaesthesia and mechanical hyperalgesia, as well as reduced conditioned pain modulation, all further supporting the notion that the chronic pain experienced by patients with PC is at least in part of neuropathic origin.…”
mentioning
confidence: 99%